The effectiveness of cognitive developmental hypnotherapy on differentiation of self, meaning in life and marital conflicts in married women. Issue 3 (11th January 2022) - Mohaghegh Toosi, Faezeh; Sharbaf, Hamidreza Aghamohamadian; Fathi, Mehdi; Kareshki, Hossein
ABSTRACT: The aim of the present study is to investigate the effectiveness of Cognitive Developmental Hypnotherapy (CDH) on Differentiation of Self, Meaning in Life and Marital Conflicts in married women. The method is quasi-experimental pretest and posttest with a control group. The statistical population of this study includes married women who came to FUM Counseling and Psychological Services Center to receive psychological services. The sample of this study included 40 married women who were selected by targeted sampling method and randomly assigned to two experimental and control groups. Participants in the pretest and posttest study answered the Differentiation of Self Inventory, the Marital Conflicts questionnaire by Sanaei, and the Meaning in Life questionnaire. The research data were analyzed using ANCOVA and MANCOVA with SPSS-21. The findings showed CDH led to an increase in Differentiation of Self and Meaning in life, and a reduction in Marital Conflicts in women. Accordingly, CDH through using techniques such as induction and empowerment of the Ego is effective in marital conflicts of married women. Therefore, using it as a means to improve the quality of married women's lives is recommended.